(untitled) (Agricultural Engineering, 2016)
In some opinion-forming environments the problem of noise emitted by wind power stations is very controversial. It is even suggested that they negatively affect the quality and length of human life. Based on the review of domestic and foreign publications an analysis of the impact of the low-frequency noise on a human being was carried out. Wind power stations operating in groups (farms) constituted the source of noise. It was proved that the level of acoustic pressure with G weighting does not exceed the value of 85 dB. The value of the admissible burdensome noise (102 dB) was exceeded in the bus cabins which were driving with the speed exceeding 30 km·h−1. The opinion of the Ministry of Health confirms the findings. It proves that the present knowledge does not allow a clear indication of the relation between the wind farms and their negative impact on the human health.